User satisfaction in energy efficiency office building in Malaysia case study: Kementerian Tenaga, Teknologi Hijau Air, Putrajaya / Siti Marina Abdullah - Abdullah, Siti Marina (Faculty of Architecture, Planning and Surveying, 2010)
User satisfaction is an essential and importance area that affects the bottom line of the owner. Nowadays, energy efficiency office building are more been developed by government in matter of reducing contribution to global warming and also cut cost. Energy efficiency also believes reducing energy wastage that brings to energy efficiency. In this research, researcher study on user satisfaction in energy efficiency office building in Malaysia in accordance to government encouragement to build more energy efficiency building. Researcher want to identify either the energy efficiency office building can make user delighted or in other words, user satisfaction or not. Through this study, energy efficiency will be identified as a guarantee to user satisfaction and comfort or in otherwise. Primary and secondary data is carried out to finish this study. Primary and secondary is used to identify current status of energy efficiency office building in Malaysia. Meanwhile, primary data is used to measure user satisfaction in energy efficiency office building.